Association Between Group Identification at School and Positive Youth Development: Moderating Role of Rural and Urban Contexts - Paricio, Diana; Herrera, Marina; Rodrigo, María F.; Viguer, Paz (Frontiers in Psychology, 2020)
These studies are framed within Social Identity Theory and the Positive Youth Development approach. The aim is: (1) to analyze the relationship between group identification at school and key positive development variables (such as self-esteem, self-efficacy, assertiveness, empathy, alexithymia, satisfaction with life, and academic performance); and (2) examine the moderator role of the context (rural or urban areas of residence) in these associations. The samples were composed of 246 adolescents from a rural context (study 1) and 156 students from rural and urban contexts (study 2). As proposed in our hypotheses, the results show statistically significant relationships between group identification and all the variables considered, higher group identification with the class in the rural context, and a moderator role of the context in the relationships between group identification and satisfaction with life, assertiveness, and empathy. These results are relevant for designing and implementing psychoeducational programs to promote positive youth development in both rural and urban contexts.